Modification of Conventional Adsorbents for CO2 Capture - Chand, Tinesh (My University, 2012)
Conventional adsorbents show high adsorption capacities at room temperature, their capacities decline with rise in temperature. Selectivity of these materials is low. Adsorption of these materials is physical adsorption rather than chemical adsorption. To overcome these limitations, conventional adsorbents need to be modified. CO2 is a Lewis acid, introduction of Lewis bases onto surface of these adsorbents may favour CO2 capture performance of these materials. Modification of conventional adsorbents can be done by many methods like amination, activation, impregnation of Fe2O3 and Cr2O promoted by Zinc on solid support. In this work, conventional adsorbents chosen was Zeolite 13X, while modification was done by monoethanol amine (MEA). Aqueous solutions of MEA of four different concentrations were prepared and agitated with crushed Zeolite 13X. Four different concentrations were 5 wt%, 10 wt%, 15 wt% and 20 wt% of MEA. Amount of MEA loaded on Zeolite13X were calculated by titrimetric analysis. Out of these solutions, 20 wt% MEA solution showed best loading. Breakthrough curves of bare Zeolite13X and modified Zeolite 13X were obtained with the help of adsorption column set up.
M.Tech. (CHED)
Keywords: Adsorbent; Carbondioxide